Hubungan Status Fisik Pra Anestesi Dengan Waktu Pulih Sadar Pasien Post Operasi Dengan General Anesthesia - Hamarno, Rudi; Arif, Taufan; Arifaen, Aditya Mauludin Afkar Nur Arij; Ciptaningtyas, Maria diah (Jurnal Keperawatan Muhammadiyah, 2024)
Introduction: The duration of recovery of consciousness in postoperative patients with general anesthesia is a common problem after the patient is transferred to the recovery room. The recovery period of patients after surgery and general anesthesia is influenced by several factors, one of which is the physical condition before anesthesia based on ASA status. The purpose of this study was to determine the relationship between ASA status and the recovery time of patients after surgery with general anesthesia in the recovery room. Method: The study design used a "cross-sectional" approach. The average population per month was 139 postoperative patients using general anesthesia aged 26-65 years. The sampling method used purposive sampling with 59 respondents. Determination of respondents was based on the inclusion criteria of patients undergoing elective surgery aged 26-65 years, patients who received ASA status 1 and 2. Data analysis tests used descriptive statistical tests to determine the characteristics of respondents. Results: Bivariate analysis used the Spearman rank test to determine the relationship between pre-anesthesia physical status and the recovery time of patients after surgery with general anesthesia. The results of the bivariate test of ASA physical status with a p-value of 0.000. Discussion: Pre-anesthesia physical status is related to the recovery time of patients after surgery with general anesthesia. Physical status conditions with accompanying illnesses can interfere with the anesthesia process and post-anesthesia recovery.